Ramadan Mengaji dan Tebar Iftar: Inovasi Program KKN STIBA Makassar dalam Menghidupkan Bulan Suci di Desa Allaere - Kasman Bakry; M. Kasim (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The STIBA Makassar Real Work Lecture Program (KKN) in Allaere Village, Tanralili District, Maros Regency is a form of implementation of the Tri Dharma pillar of Higher Education, namely community service. This research aims to optimize community religious development through various activities designed based on local needs. This research examines the effectiveness of implementing the KKN program in improving the religious and social quality of society. The implementation method begins with mapping community needs using the SOAR Analysis (Strengths, Opportunities, Aspirations, Results) approach, which aims to provide a comprehensive picture of potential, opportunities, aspirations and expected results. Based on this analysis, relevant work programs were prepared, including activities such as the Imam program and Tarawih Lectures, Kindergarten/TPA Teaching, Teaching in Schools, Imams and Friday Sermons, Social Activities, Ramadan Koran Recitation and Iftar Distribution, Iktikaf and Evening Prayers, Children's Festivals Saleh, Funeral Service Training, and Kilat Islamic Boarding School. The results of this research show success in achieving the main goal of KKN, namely providing a significant contribution to religious formation and empowerment in realizing an Islamic society and also strengthening social interaction between students and local residents.